Reforming pensions in Europe: Economic fundamentals and political factors - Ondřej Schneider (Charles University in Prague, Institute of Economic Studies (IES), 2009)
This paper analyzes pension reforms in Europe and their determinants. As pension reforms are intrinsically difficult to define and pinpoint, we introduce an alternative measure of pension reforms by comparing long-term forecasts of pension expenditures for seventeen European countries. The larger the decrease in expected spending on public pensions in 2050 between two base years, the more successful a pension reform the country achieved (after controlling for other factors, such as demography). Our analysis shows that the reform effort varies widely across countries and over time. Indeed, only three countries in the EU managed to reduce their expected spending on pensions in both reference periods. In the second part of the paper, we analyze factors that may facilitate or hamper pension reform quality of fiscal institutions, public debt, trade unions' influence, and also demographic factors. Only the measure of trade union power proves to be significant in explaining pension reforms. Other factors, such as quality of fiscal institutions, size of the existing funded pillar, public debt or recent demographic developments, do not seem to play a significant role. However, specific pension system factors most significantly the lagged change in pension expenditures are significant and suggest that European governments do reform their pension systems when faced with the threat of escalating pension expenditures. In conclusion, we propose a hypothesis of bounded economic rationale of European governments, as they seem to react to expectations of an increase in pension spending, but they seem to be content with the current spending levels. The appendix gives detailed information on pension reforms in the ten Central and Eastern European countries that became EU members in 2004 and 2007 (EU-10).
Keywords: D72; H55; P26; 330; pension system; European Union; pension reform; fiscal institutions; Gesetzliche Rentenversicherung; Rentenreform; Rentenfinanzierung; Öffentliche Sozialausgaben; Bevölkerungsökonomie; Neue politische Ökonomie; Gewerkschaftsmitgliedschaft; EU-Staaten; EU-Staaten (Osteuropa)